A solar PTC powered absorption chiller design for Co-supply of district heating and cooling systems in Denmark. (15th February 2020) - Arabkoohsar, A.; Sadi, M.
Abstract: This is quite common to supply the heating demand of absorption chillers via the local district heating system. This can be technically challenging during summer when the district heating system does not have enough load to take advantage of the high-temperature discharged flow from the absorption machine. In this study, employing parabolic trough solar collectors for the co-supply of a major heating demand of the chiller and district heating network is proposed. As the expansion of district heating systems for the newly built areas is mainly implemented in lower supply temperatures, the proposed solution works more cost-effective for such cases. The proposed solution is thermodynamically analyzed for an entire year in a case study. The results show that the system totally resolves the technical problem of the case study, offers a significant contribution to supply the district heating demand and presents an impressively better economic index compared to the conventional configuration. Results show that heat demand of the chiller is zero for one-third of the year, the system feeds district heating with a heat supply rate of over 1 MW for about three months, and the internal rate of return of the system is 5.7% for 8 years of operation. Highlights: Solar-driven absorption chiller used to supply district heating and cooling. Nearly 40% of the cases, solar field provides 14 kg/s hot water. Nearly 60% of the cases, solar field has no contribution in heat production. 25% of the cases, solar supplied heat is more than 1 MW. The IRR value was found to be 5.7%.